An award system for gamification in higher education - Lopes, Rui Pedro (2016)
Higher Education Institutions (HEI) have the missions of education, at a high level, research and cooperation. Regarding education, HEI must create an appropriate environment for learning, towards high-level academic performance. The conciliation of education and research paves the way for an adequate learning environment, further reinforced by the students' motivation. Motivation depends on several factors, some of them external, such as earning money, gaining social status, have a higher grade, and/or internal (intrinsic), which results from the person's core self (associated to the satisfaction people feel when doing something appealing). This paper describes the approach to applying gamification to a higher education subject in the course of computer science. It uses several game design mechanisms, such as adaptive challenges, rewards, curiosity and chance to increase the time students spend working, experiencing and learning in a HEI. The sections in the subject's curriculum are transformed into levels, awarding stars for increasingly complex achievements. Grades depend on the learning experiences students' choose, as well as on the time spent solving the challenges presented to them. There is also the concept of soft currency, which we call BitPoints, that can be used to increase the student autonomy and reduce the workload. An online platform is constantly available to inform the student about his or her progress within the subject as well as the grade at the moment of the access. Each level is represented by a castle on a map, which is considered conquered as soon as the student solves the required challenges. Depending on the difficulty of the challenges faced, the student can face a lower grade or a higher grade. Only after finishing all the levels, the student is able to successfully finish the subject. Virtual money can be spent in a virtual shop, where the student can invest in tools that can help solving some tasks. The virtual shop provides scripts, instructions and other techniques that can be valuable to students. A chance factor is also considered in the shop, giving further motivation to students. In the preliminary assessment of the process, students demonstrate willingness to compete not only to pursue the highest grade but also on the amount of collected BitPoints and on the speed to complete a level. Moreover, students frequently come back to previous levels and learning experiences, to further test the acquired skills.